Kant und das Projekt der Aufklärung heute - Willaschek, Marcus (Con-Textos Kantianos. International Journal of Philosophy, 2023)
After a brief recapitulation of the most important aspects of Kant's conception of enlightenment and a side glance at Horkheimer's and Adorno's critique of enlightenment, this paper explores the question of whether Kant's conception of enlightenment is still relevant in the age of fake news, Facebook and filter bubbles. The starting point is the question of what distinguishes Kant, who was sceptical of vaccination, from today's radical anti-vaccinationists. With regard to Kant's concept of enlightenment, this raises two questions: first, what else is necessary for the ability to think for oneself (Selbstdenken) except courage to make independent use one's understanding; and second, what else is necessary for the social process of enlightenment than freedom of the press. Both questions have a Kant-critical point, for they are directed against two of Kant's explicit assertions, namely that immaturity is based on a lack of courage and that enlightenment requires no more than freedom of the press. But as will be shown, Kant himself sets these reductions right in the further course of his reflections. In fact, he gives the same answer to both of our questions, namely that thinking for oneself consists in following generally accessible („communicable“) reasons.